A Piece-Wise Linearization PID Control of Aero-engine Software Defined Control System. (May 2019) - Ji, Xiaoxiang; Li, Jianghong; Ren, Jiao; Wu, Yafeng
Abstract: A scheme of piece-wise linearization PID control of aero-engine software defined control system based on wireless network is proposed in this paper. The characteristic of the system is that the PID controller is separated and distributed among the nodes of the wireless network, each node has the function of computing, memory and wireless communication, no core control unit in the system and the whole wireless network acts as a distributed PID controller. The linearization model and corresponding tuning parameters at different working points in flight envelope of the aero-engine are established offline using the memory resource of each node to make the node task parameters switch when the aero-engine working at different points. Finally, MATLAB/Simulink software tool is used to conduct the digital simulation analysis, the result shows that the proposed scheme achieves good dynamic and steady-state performance, and achieves good control effect.